Rolling tetrahedron

A regular tetrahedron is resting on a surface. Every second, the tetrahedron rolls over onto a different face. The direction that it rolls in is uniformly random and independent (i.e. when the tetrahedron is resting, there is a 1/3 chance that it will roll in any one of three possible directions during that second).

Let a n a_n be the probability that after n n rolls (seconds), the tetrahedron will be resting on the same face that it started on.

Find:

log 3 ( 4 a 98 1 ) -\log_3(4a_{98}-1)

Can anyone tell me if it is possible to generalize this result for other polyhedra? After some labor, I was able to derive simple explicit formulae for a n a_n on the other Platonic solids (sans icosahedron).


The answer is 97.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Otto Bretscher
Jan 1, 2016

We have a n = 1 3 ( 1 a n 1 ) a_n=\frac{1}{3}(1-a_{n-1}) since there is a 1/3 chance that the tetrahedron will roll over to the original face if it's currently sitting on a different face. If we consider the difference from the equilibrium, d n = a n 1 4 d_n=a_n-\frac{1}{4} , we find the recursion d n = ( 1 3 ) n d 0 = ( 1 3 ) n 3 4 = ( 1 ) n 3 n 1 4 d_n=\left(-\frac{1}{3}\right)^nd_0=\left(-\frac{1}{3}\right)^n\frac{3}{4}=\frac{(-1)^n}{3^{n-1}4} so a n = 1 4 + ( 1 ) n 3 n 1 4 a_n=\frac{1}{4}+\frac{(-1)^n}{3^{n-1}4} . For even n n we have log 3 ( 4 a n 1 ) = n 1 \log_3(4a_n-1)=n-1 , so, the answer is 97 \boxed{97} for n = 98 n=98 .

Moderator note:

Great approach. In this case, because all faces are the same (we can go from any face to any other face), the analysis is much easier.

If we wanted to deal with the cube, then we will have to consider the opposite face as seperate.

Andreas Wendler
Jan 1, 2016

Yes Sir. Got same solution but as physicist found it by induction of course! Considering the probabilities for increasing n (3/9; 6/27; 21/81; 60/243 etc.) obtained formula: 1 3 n ( ( 1 ) 2 3 n 1 + ( 1 ) 3 3 n 2 + . . . + ( 1 ) n 3 ) = 3 n 1 + ( 1 ) n 4 × 3 n 1 \frac{1}{3^{n}}((-1)^{2}3^{n-1}+(-1)^{3}3^{n-2}+...+(-1)^{n}3) = \frac{3^{n-1}+(-1)^{n}}{4 \times 3^{n-1}} .

So finally the solution of the problem was reduced to the determination of a sum formula for an alternating row.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...